Q: WHAT IS 3P equals 6?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

==>-3p+7=5-8p+6 ==>5p+7=11 ==>5p=4 ==>p=4/5

3p +12= 7p 7p-3p=12 12?3=4 p=4

100 - 3p = 88 -3p = 88 - 100 -3p = -12 p= (-12/-3) p = 4 so 100 - 3 * 4 = 88

3p = 2p + 12subtracting 2p from both sidesp = 12 ■

3p+5+p = -23 3p+p = -23-5 4p = -28 p = -7

Related questions

If: 6p-2-3p = 16 Then: p = 6

==>-3p+7=5-8p+6 ==>5p+7=11 ==>5p=4 ==>p=4/5

3p - 6 > 21 3p - 6+6 > 21+6 3p > 27 3p/3 > 27/3 p>9 this WILL help

p=10/3 or 3.33333333333333333333333333333333333333333333333333333333333333333333333333333

3p plus 7 equals 34, where P is equivalent to number 9.

3p +12= 7p 7p-3p=12 12?3=4 p=4

3p + 6 = 4p + 6 This implies that, 3p - 4p = 6 - 6 -1p = 0 Therefore, p = 0/-1 = 0

3p - 6 > 213p - 6 + 6 > 21 + 63p > 273p/3 > 27/3p > 9

4p+2 = 3p-7 4p-3p = -7-2 p = -9

3p+7 = 16+2p 3p-2p = 16-7 p = 9

100 - 3p = 88 -3p = 88 - 100 -3p = -12 p= (-12/-3) p = 4 so 100 - 3 * 4 = 88

13 + 3p = -2subtract 13 from each side, 3p = -15divide each side by 3, p = -5